PEMBERDAYAAN PETERNAK BABI MELALUI PEMBENTUKAN KELOMPOK DAN PENGUATAN PEMASARAN KOLEKTIF DI GUNUNG NONA, KOTA AMBON - Jomima Martha Tatipikalawan; Michel Johan Matatula; George Semuel Johny Tomatala (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
Pig farming in Gunung Nona, Ambon City, has significant economic potential but still faces challenges related to traditional and limited marketing systems. This community service program aimed to enhance farmers’ capacity through group formation and strengthening collective marketing based on social media. The methods included preparation, extension activities, group formation, social media training, as well as evaluation and mentoring. The results showed the establishment of an organized recognized farmer group, along with improved knowledge and skills in utilizing digital platforms such as Facebook, Instagram, and WhatsApp Business. Farmers were able to create social media-based promotion manage business accounts, and communicate directly with consumers. In addition, farmers demonstrated increased confidence in marketing their products more widely without relying on intermediaries. This program contributed to the transformation of marketing systems from conventional to more effective and efficient digital approaches. Therefore, empowerment through institutional strengthening and digital marketing is a strategic approach to improving competitiveness and sustainability of small-scale pig farming businesses.